Futurologi Undang-undang Pemilu di Indonesia Perspektif Maqāṣid al-Sharī‘ah - Muhaimin Muhaimin; Abd Wahab (Islamica: Jurnal Studi Keislaman, 2019)
This article is a response to some regulations of the election in Indonesia, facing the General Election of 2019. This article will make a more complete analysis than before, yet the people over the general election a few years ago based on the regulation. Even, inside the process, there are many issues that must be concealed in future time. So, this article also gives a new paradigm based on maqāṣid al-sharī‘ah become a foundation to formulate the next. This article concludes that for the future, to get all coherences of maqāṣid al-sharī‘ah in ideal concepts, the regulators must be put al-maṣlaḥah al-‘āmmah as a core. Al-Maṣlaḥah al-‘āmmah means that regulations will erase the contestation of political identities, strengthening the presidential system, and regulate over the money politics on the campaign process in the future election.